Breast cancer incidence and mortality: trends over 40 years among women in Shanghai, China. (18th February 2016) - Huang, Z.; Wen, W.; Zheng, Y.; Gao, Y. T.; Wu, C.; Bao, P.; Wang, C.; Gu, K.; Peng, P.; Gong, Y.; Zhang, M.; Xiang, Y.; et al.
Abstract : With 40 years of cancer data from the oldest population-based cancer registry in China, this study evaluates secular time trends in breast cancer incidence and mortality in an urban Chinese population. Our results show a tremendous increase in incidence and a slight increase in mortality with significant age, cohort, and period effects for breast cancer among women in urban Shanghai. Abstract: Background: Breast cancer incidence rates are increasing among Asian women, likely due to the changes in risk factors caused by globalization. Trends in breast cancer rates among Chinese women may differ from other Asian regions due to the implementation of a nationwide family planning program and resulting changes in women's reproductive practices. Appraisal of cancer trends can direct cancer control and public health planning, but relevant studies in China are scarce due to a lack of long-term data. We sought to evaluate secular time trends in breast cancer incidence and mortality using 40 years of cancer registry data for women in urban Shanghai. Materials and methods: Data on invasive breast cancer incidence and mortality were collected by the Shanghai Cancer Registry. Age-standardized rates (ASRs) for incidence and mortality were calculated using the Segi/Doll 1960 world standard population. Age, period, and birth cohort effects were evaluated using age–period–cohort (APC) Poisson regression models. Overall linear trends, interpreted as the estimated annual percentage change (EAPC), were derived from the net drift in age–drift models. Results: A total of 53 885 breast cancer cases and 17 235 breast cancer-specific deaths were documented among women in urban Shanghai between 1 January 1973 and 31 December 2012. Breast cancer incidence and mortality ASRs increased by 141.2% and 26.6%, respectively. Significant age, cohort, and period effects were identified in both incidence and mortality APC models; cohort effects were pronounced. Overall, a substantial increase in breast cancer incidence (EAPC = 2.96%/year) and a moderate increase in breast cancer mortality (EAPC = 0.87%/year) was observed. A notable downward trend in mortality was identified among younger women born after 1960. Conclusions: Forty years of cancer registry data document a tremendous increase in incidence and a slight increase in mortality for breast cancer among women in Shanghai. Effective, appropriate, and affordable breast cancer prevention and control strategies are urgently needed in China.